2016
DOI: 10.1038/srep25638
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adsorptive removal of p-nitrophenol from water by aluminum metal–organic framework/reduced graphene oxide composite

Abstract: In this study, the composite of aluminum metal–organic framework MIL-68(Al) and reduced graphene oxide (MA/RG) was synthesized via a one–step solvothermal method, and their performances for p–nitrophenol (PNP) adsorption from aqueous solution were systematically investigated. The introduction of reduced graphene oxide (RG) into MIL-68(Al) (MA) significantly changes the morphologies of the MA and increases the surface area. The MA/RG-15% prepared at RG-to-MA mass ratio of 15% shows a PNP uptake rate 64% and 123… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…k 1 (min − 1 ) is the rate constant that is related to the adsorption equilibrium rate. e plot of the pseudo-first-order model is from log (Q e -Q t ) versus t. e pseudo-second-order model originated from Wu et al [28]. e model is expressed as follows:…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…k 1 (min − 1 ) is the rate constant that is related to the adsorption equilibrium rate. e plot of the pseudo-first-order model is from log (Q e -Q t ) versus t. e pseudo-second-order model originated from Wu et al [28]. e model is expressed as follows:…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Liang et al [148] found that with the increase of GO introduced in GO@MIL-101, both the integrity of the crystal composite and particle size were reduced, while with an appropriate dose the maximum capacity of adsorption for Cr (VI) could reach 125 mg•g −1 with GO@MIL-101, which was 20% higher than that achieved with MIL-101. Wu et al [149] synthesized a composite (MA/RG) using aluminum-based MOFs (MIL-68 (Al)) and reduced graphene oxide (RG) through a one-step solvothermal method. An adsorption experiment for liquid p-nitrophenol (PNP) was conducted, showing that introducing reduced graphene oxide (RG) could significantly alter the morphology of MIL-68 (Al), thus increasing the size of its surface area.…”
Section: The Coupling Of Mofs With Graphenementioning
confidence: 99%
“…The medium band gap, along with low cost, simple preparation method, high chemical stability, and non-toxicity, makes g-C 3 N 4 appropriate for photocatalytic applications, including organic pollutant degradation, water splitting, CO 2 reduction and organic synthesis under visible light [22][23][24][25][26]. In addition, g-C 3 N 4 has found application in optical and electronic devices, chemical sensors, and energy generation/storage [23,[27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%